Defining Polyamory - Cardoso, Daniel (2021)
This study aimed to analyze laypeople’s defnitions of polyamory and compare defnitions presented by people who are not willing to engage in consensual non-monogamy (CNM) and those who are or are willing to be in a CNM relationship. This exploratory qualitative study used data collected from a convenience sample through a web survey, where people answered the question “What does polyamory mean?” We conducted thematic analysis to examine patterns in meaning and used demographic data to compare themes among groups. The fnal sample comprised 463 participants aged 18–66 years (M=32.19, SD=10.02), mostly heterosexual (60%). Of the total sample, 54% were in a monogamous relationship, followed by 21% not in a relationship, and 13% in a non-monogamous relationship. Analysis showed that people defne polyamory mostly as a set of behaviors in a relationship, followed by the potential of multiple relationships or feelings for multiple people. Defnitions also include emotional, sexual, and ethical aspects. People in CNM relationships are more likely to defne polyamory as constituting a potential form of relating, focus more on interpersonal feelings and ethics, and include consent in their defnitions than those unwilling to engage in CNM. People in CNM relationships also focus particularly on the non-central role of sex within these relationships, which might challenge assumptions about sexuality in these relationships in clinical and research settings.